Antiparasitic Activities of Compounds Isolated from Aspergillus fumigatus Strain Discovered in Northcentral Nigeria - Oluwatofunmilayo A. Diyaolu; Gagan Preet; Adeshola A. Fagbemi; Frederick Annang; Guiomar Pérez-Moreno; Cristina Bosch-Navarrete; Olusoji O. Adebisi; Emmanuel T. Oluwabusola; Bruce F. Milne; Marcel Jaspars; Rainer Ebel (MDPI AG, 2023)
In this study, we explored a fungal strain UIAU-3F identified as Aspergillus fumigatus isolated from soil samples collected from the River Oyun in Kwara State, Nigeria. In order to explore its chemical diversity, the fungal strain UIAU-3F was cultured in three different fermentation media, which resulted in different chemical profiles, evidenced by LC-ESI-MS-based metabolomics and multivariate analysis. The methanolic extract afforded two known compounds, fumitremorgin C (1) and pseurotin D (2). The in vitro antiparasitic assays of 1 against Trypanosoma cruzi and Plasmodium falciparum showed moderate activity with IC50 values of 9.6 µM and 2.3 µM, respectively, while 2 displayed IC50 values > 50 µM. Molecular docking analysis was performed on major protein targets to better understand the potential mechanism of the antitrypanosomal and antiplasmodial activities of the two known compounds.